An Exploration Respond of COVID-19 Policy through Social Media in Indonesia - Bambang Irawan; Mohammad Jafar Loilatu; Paisal Akbar; Rizky Reynaldi (Policy & Governance Review, 2022)
This paper explores public responses through social media to the COVID-19 policy in Indonesia; public response to the COVID-19 policy shows that information about COVID-19 is sourced from crowd sources, thus creating misinformation on health information. To answer the research purpose, this research uses NodeXL to explore policy responses through social media Twitter; data collection was carried out from 3-25 July 2021. The result shows the public response to the COVID1-19 policy in Indonesia through topic distribution on social media Twitter. From these findings, 10 topics on social media became public responses to COVID-19 policies. This topic addresses the public's response to the COVID-19 condition in Indonesia and the policies taken by the government. We classify these topics based on the characteristics of public responses that indicate certain conditions such as vaccine policies, medical device crises, hoax information, collaboration, and political conditions. However, this research has limitations on access to the data taken. Therefore, further research can explore the function of social media in post-COVID-19 policies.